Preventing hepatitis C virus transmission among young people in the justice system - Lenton, E.; White, B.; Aitken, C.; Hellard, M.; Higgs, Peter (Elsevier, 2013)
Young people involved with the criminal justice system have been identified as a group at high risk of hepatitis C virus (HCV) infection. This study was designed to explore the feasibility of assessing an individualised structured HCV prevention intervention among young people recruited from post release agencies and youth drug and alcohol services in Victoria, Australia. The focus of the intervention was to extend the intensive, individualised, psychosocial-focused services provided to young people by these agencies to include HCV testing and prevention. Results demonstrate that it is possible to implement a randomised controlled trial of a HCV prevention intervention among vulnerable young people. Our data suggest that placing a specialised HCV worker alongside youth-focused post-release services is feasible and acceptable to both young people and the majority of service staff in the context in which we implemented this intervention.